Promotion and Inhibition of Iron Accumulation in Soybean Plants - Elmstrom, G. W. (1970)
Plants of four soybean (Glycine max L. Merrill) genotypes differing in their ability to accumulate iron were studied. The efficient genotypes were Hawkeye (HA) and A62-9 (E-9), and the inefficient ones were PI-54619-5-1 (PI) and A62-10 (I-10). When plants of opposite efficiency were grown in the same solution, iron accumulation decreased in the primary leaves of efficient plants, but it was unaffected or slightly reduced in the leaves of inefficient plants. Absorption of iron during a 24-hour period by 17-day-old plants indicated that solutions in which either HA or PI plants had been previously cultured contained a heat-labile factor which increased iron accumulation by iron-stressed HA plants. Also, it was found that HA plants from mixed culture accumulated about 50% less iron than HA plants grown in pure culture, independent of the absorption solution used. The conditions described, therefore, may either stimulate or inhibit iron accumulation in efficient soybean plants.